Dialogue isn't working: the case for collaboration as a model of legislative–judicial relations. (27th December 2015) - Carolan, Eoin
Abstract : In the past two decades, it has become commonplace for legislative–judicial engagement on contested constitutional questions to be described as a dialogue. This paper argues that the time has come to abandon the notion of dialogue. The first part of the paper describes the difficulties with dialogue theories. Despite the existence of many different versions, these theories share certain constitutionally problematic characteristics. Dialogue theories promote a view of government that is unrealistic, susceptible to normative bias and that overlooks the critical importance of disagreement and institutional differences to a system of democratic government based on the rule of law. The second part of the paper argues that Christopher Ansell's idea of collaboration‐as‐fruitful‐conflict provides a more descriptively and normatively appropriate account of the relationship between the legal and political branches of government.